Legal Challenges and Policy Implications for Property Rights Protection in Uzbekistan - Bakhromjon Rakhimjonovich Topildiev; Yunus Mukhitdinovich Khodjiev; Nuriddin Aktam ugli Shermatov; Asalya Sultonmurodovna Kayumova; Dildora Elmuradovna Abdullaeva (Journal of Human Rights, Culture and Legal System, 2026)
Property rights protection in Uzbekistan has been supported by various legal policies and institutional frameworks; however, its practical effectiveness remains limited. This study aims to examine the underlying causes of these deficiencies, particularly focusing on the lack of doctrinal clarity, inconsistent categorization of legal remedies, and disparities in judicial practices, especially in compensation disputes and land acquisition cases. The research employs a normative legal methodology, incorporating legislative, conceptual, historical, case-based, and comparative approaches to provide a comprehensive analysis. The findings indicate that Article 164 of the Civil Code establishes a solid normative basis by recognizing the rights to own, use, manage, and protect property. Nevertheless, the historical evolution of the legal system, shaped by Islamic and customary traditions, Soviet-era state control, and post-independence reforms, has contributed to persistent inconsistencies in judicial application. The study further identifies key challenges in determining ownership, distinguishing between proprietary and obligational claims, and ensuring uniformity in judicial decisions related to compensation and public interest. Comparative insights demonstrate the importance of coherent legal interpretation, precise legal definitions, and transparent remedial mechanisms. This study concludes that strengthening the legal framework and promoting consistent judicial enforcement are essential to ensuring effective and reliable property rights protection in Uzbekistan.